SCROOGE'S CHARACTER DEVELOPMENT IN CHARLES DICKENS' A CHRISTMAS CAROL - Theresia Erwindriani (Celt: A Journal of Culture, English Language Teaching & Literature, 2012)
This paper deals with Scrooge's characterization in Dickens' A Christmas Carol who is a rich, cold-hearted, miserly, misanthropy, and an anti Christmas old man. He experiences a gradual character development that comes from his awareness of his bad character and from the ghosts and other characters after seeing the visions of his past, present and future shown by the ghosts on Christmas Eve. Yet on Christmas Day, he becomes an altered old man, by being a kind, warm, generous old man to everyone, especially to the poor and a person who honors Christmas and has Christmas spirit in his heart. This study uses the formalistic approach to analyze Scrooge's character development, by focusing on A Christmas Carol's text. In studying about Scrooge's characterization, Charles Dickens' message, namely charity is also proven. With charity, Dickens shows that people can especially help the poor and make them happy.